Correlation between activation of PI3K/AKT/mTOR pathway and prognosis of breast cancer in Chinese women. - Ling Deng; Jie Chen; Xiao Rong Zhong; Ting Luo; Yan Ping Wang; Hui Fen Huang; Li-Juan Yin; Yan Qiu; Hong Bu; Qing Lv; Hong Zheng (PLoS ONE, 2015)
Abnormal activation of PI3K/AKT/mTOR (PAM) pathway, caused by PIK3CA mutation, KRAS mutation, PTEN loss, or AKT1 mutation, is one of the most frequent signaling abnormalities in breast carcinoma. However, distribution and frequencies of mutations in PAM pathway are unclear in breast cancer patients from the mainland of China and the correlation between these mutations and breast cancer outcome remains to be identified.A total of 288 patients with invasive ductal breast cancer were recruited in this study. Mutations in PIK3CA (exons 4, 9 and 20), KRAS (exon 2) and AKT1 (exon 3) were detected using Sanger sequencing. PTEN loss was measured by immunohistochemistry assay. Correlations between these genetic aberrations and clinicopathological features were analyzed.The frequencies of PIK3CA mutation, KRAS mutation, AKT1 mutation and PTEN loss were 15.6%, 1.8%, 4.4% and 35.3%, respectively. However, except for PTEN loss, which was tied to estrogen receptor (ER) status, these alterations were not associated with other clinicopathological features. Survival analysis demonstrated that PIK3CA mutation, PTEN loss and PAM pathway activation were not associated with disease-free survival (DFS). Subgroup analysis of patients with ER positive tumors revealed that PIK3CA mutation more strongly reduced DFS compared to wild-type PIK3CA (76.2% vs. 54.2%; P = 0.011). PIK3CA mutation was also an independent factor for bad prognosis in ER positive patients.AKT1, KRAS and PIK3CA mutations and PTEN loss all exist in women with breast cancer in the mainland China. PIK3CA mutation may contribute to the poor outcome of ER positive breast carcinomas, providing evidence for the combination of PI3K/AKT/mTOR inhibitors and endocrine therapy.